Numerical simulation of brittle damage in concrete specimens - Labadi, Y.; Hannachi, N.E. (Проблемы прочности, 2005)
A framework for damage mechanics of concrete
is applied to simulate the non-linear elastic
deformation behavior of concrete using
finite element method (FEM). A rather simple
isotropic damage model containing essentially
no adjustable parameters is shown to produce
results in remarkably good agreement with sample
experimental data: the damage law requires
only the fracture energy to be defined completely.
The model is achieved by introducing a
damage surface that is similar to the yield function
in the conventional theory of plasticity. A
special form of damage surfaces is constructed
to illustrate the application of the model. A new
damage criterion, defined as an equivalent
strain norm, is proposed, in order to take into
consideration the asymmetric behavior of concrete.
For verifying the FEM program including
the model, deformations predicted by this
model are compared with both the experimental
ones for the concrete structural model and
the ones calculated without application of the
continuum damage mechanics. Запропоновано критерій руйнування конструкцій з бетону, що отримав назву
норми еквівалентних деформацій. Критерій дозволяє враховувати асиметричну
механічну поведінку бетону при розтязі та стиску. Розроблено ізотропну
модель, що базується на використанні поверхні пошкодження, яка аналогічна
функції плинності теорії пластичності. За допомогою запропонованої
моделі виконано скінченноелементний розрахунок нелінійно-пружної деформації
зразків із бетону. Проведено порівняння отриманих результатів з експериментальними.
Установлено, що точність розрахунків більш висока, аніж
прогнози без використання підходів механіки пошкодження твердого тіла. Предложен критерий повреждения конструкций из бетона, получивший название нормы
эквивалентных деформаций, который позволяет учитывать асимметричное механическое
поведение бетона при растяжении и сжатии. Разработана изотропная модель, базирующаяся
на использовании поверхности повреждения, аналогичной функции течения теории
пластичности. С помощью предложенной модели выполнен конечноэлементный расчет
нелинейно-упругой деформации образцов из бетона. Проведено сравнение полученных результатов
с экспериментальными. Показана хорошая корреляция между расчетными и экспериментальными
результатами. Установлено, что точность расчетов более высокая по
сравнению с прогнозами, выполненными без применения подходов механики повреждения
твердого тела.